Assessing Teachers' Attitude toward adopting KHDA framework for Special Education Needs in UAE - YOUSSEF, ZEINA (2019)
The educational system is moving toward including students with disabilities in mainstream schools. This remarkable move is not an easy process since the schools’ culture is still in its primary stages regarding inclusive settings. For inclusion to succeed, many practitioners should be involved to make this successful change. As inclusion has seemingly become the preferred placement for students with disabilities, teachers’ attitude toward including students with disabilities has become an important variable in creating a successful inclusion program. Recently UAE has updated its framework for inclusion. KHDA in its new framework highlighted the importance of the action team in successful inclusion. The action team according to the new framework includes champions, governors, support assistants and strategic planners. This study aims to investigate the feasibility of adopting the new KHDA inclusion framework. It also examines school barriers for adopting the new inclusion provisions. The variables that are considered in this study covered both operational and strategic factors. Among those factors, teachers’ attitude towards the new provision was investigated for the purpose of this study mixed research method was used. A survey was conducted to measure and correlate the intended factors. The questionnaire comprised of both close and open-ended questions, the intention behind to get an in-depth information that would be generalizable at the same time. The findings of both qualitative and quantitative analysis were triangulated with document analysis. The study aims to investigate the feasibility of adopting the new KHDA inclusion framework. It also examines school barriers for adopting the new inclusion provisions. The outcomes generally revealed that competency among teachers remains an integral aspect of ensuring that the students receive the necessary training while in school. The study identified various concerns within the learning program that need to be addressed without complicity as the government sought to invoke collaborative education within the KHDA framework.